Effect of Barium Hexaferrite Doped Yttrium (Y3+) On The Microwave Absorption By Solid-State Reaction Methods - Sihotang, Muhammad Sontang; Angelo, Marc Antonio; Naibaho, Marzuki; Maulidita, Maulidita; Ichsan, Novita; Ginting, Masno (Talenta Publisher, 2025)
Yttrium-substituted M-type barium hexaferrite was successfully synthesized using the solid-state reaction method. X-ray diffraction (XRD) confirms that all various samples have a single phase (for x = 0,0 and 0,1), have increased trend for crystal size (from 56,99 to 59,34 nm), cell volume (from 697,9161 to 701,2375 Å), and lattice parameter (a = 5,8948 to 5.9024 and c = 23,1918 to 23,2422) caused by ion substitution increased. SEM-EDX figure shows that the particle shape of yttrium-doped barium hexaferrite is hexagonal, and there is a growth in particle size as the amount of doping increases from 1.050 to 1.202 µm, and also the amount of Y3+ ion doping increases, the number of Fe atoms decreases, and the number of Y atoms increases. The materials were characterized using a Vector Network Analyzer (VNA), which shows a minimum reflection loss of x = 0.1 reaching -7,34 dB in the X-band for a thickness of 1.5 mm, better sample variation when compared to other sample variations.